Aplikasi Metode Economic Order Quantity (EOQ) Terhadap Total Biaya Persediaan Bahan Baku Makanan Groceries & Dairy Product Di Banana Inn Hotel Kota Bandung - Nadia Putri, Naila; Sudono, Agus; Riyadi, Doni (Universitas Pendidikan Indonesia, 2016)
Availability of material product is process that important for given goodservice to consumer. In supplying material product have to notice cause of theresult of production will be influential in inventory material product. Thisresearch based on surplus and shortage in material product in storage. BananaInn Hotel Bandung havenâ€™t had control system of purchases and controlling ofmaterial product of groceries. Economic Order Quantity (EOQ) method is one ofcontrolling material product that will determine of efficiency cost. The purpose ofÂ this research is for comparing method between in Banana Inn Hotel Bandungwith EOQ method in efficiency of total inventory material product of groceries inBanana Inn Hotel Bandung.Research method of this research is experiment method. Data that used inthis research is secondary and primery data base on total needed of purchasingmaterial product groceries at December 2015 â€“ March 2016 and there areordering cost and storage cost in Banana Inn Hotel Bandung. Technique analysisdata of this research is EOQ method and efficiency total cost of inventory.The result of this research had gotten based on research that had done withEOQ method given that efficiency total cost of inventory of material productgroceries dairy product is 17,5%. Method of EOQ also used in company andwill give efficiency cost in Banana Inn Hotel Bandung.